REFLECTIONS ABOUT THE PEDAGOGICAL TREATMENT OF PHYSICAL EDUCATION IN HIGH SCHOOLS: A FOCUS ON CONTENT AND OBJECTIVES. (Fiep Bulletin - online, 2013)
The present study investigates the pedagogical treatment of Physical Education as well as the objectives and the content that drive the performance of teachers. The method used was a literature research to understand the pedagogical approach, the contents and applied objectives, seeking references and authors who discuss such issues in high schools. It was observed that in schools, the content taught in Physical Education classes is not always suggested by the National Curriculum and the Law of Guidelines and Bases of National Education, showing that, in most cases, teachers use more sports content than bodily activities such as games, gymnastics, wrestling and dancing. I realized the need for a reorganization of proposed plans, enabling better approaches and contents to be developed in high school. I believe that Physical Education collaborates in the training of the students and their active participation in society.
Keywords: physical education; high school; reflections.